Challenges of applying artificial intelligence responsibly at scale in healthcare - Brinhosa, Amanda Furtado; Fernandes, Elizabeth Rocha; Figueroa, Rafael de Castro; Silva, André Vinícius Rocha; Drabowski, Nicholas Roberto (Journal of Health Informatics, 2021)
Objective: This article aims to present a case study on the main challenges of applying artificial intelligence (AI) in a scalable manner, following the precepts of the research field on responsible AI in the health area. Method: During the referred period, data were collected on operation, medical reports and examinations of the telemedicine system studied, which were analyzed and compared in different ways. Results: As a result, two different perspectives of the theme were defined, one regarding operational requirements, which are linked to the daily use of such technology, and another to technical requirements, which are related to the essential characteristics of these tools. Both were illustrated through reports and data from practical and real examples. Conclusion: From this set of information, some more critical points were raised and discussed, highlighting the caution necessary to work with AI in health and its benefits.